2017
DOI: 10.1097/mao.0000000000001489
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Intraoperative Testing on Surgical Decision-making During Cochlear Implantation

Abstract: Our data suggest that with respect to CI in children and adults in straightforward cases (e.g., normal anatomy, nondifficult insertion, etc.), routine intraoperative evoked compound action potentials, impedances, and imaging rarely influence surgical decision-making in our clinic and may have limited usefulness in these patients. The implications of this are discussed and a review of the literature is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…ECAP may be absent secondary to air bubbles within the cochlea, which affect electrophysiologic testing. 6 Since ECAP is a measure of spiral ganglion and cochlear nerve function, absent ECAP may be the result of severe dysfunction of these neural elements in the auditory pathway. 11 Interestingly, Eftekharian et al 17 found statistically significant increases in intraoperative ECAP thresholds with increased depth of anesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…ECAP may be absent secondary to air bubbles within the cochlea, which affect electrophysiologic testing. 6 Since ECAP is a measure of spiral ganglion and cochlear nerve function, absent ECAP may be the result of severe dysfunction of these neural elements in the auditory pathway. 11 Interestingly, Eftekharian et al 17 found statistically significant increases in intraoperative ECAP thresholds with increased depth of anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Several causes for absent intraoperative ECAP have been hypothesized. ECAP may be absent secondary to air bubbles within the cochlea, which affect electrophysiologic testing 6 . Since ECAP is a measure of spiral ganglion and cochlear nerve function, absent ECAP may be the result of severe dysfunction of these neural elements in the auditory pathway 11 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations